Defensive mutualisms: do microbial interactions within hosts drive the evolution of defensive traits?. (2nd October 2013) - May, Georgiana; Nelson, Paul; Clay, Keith
Summary We examine theoretical and empirical results to determine the importance of microbe–microbe interactions in the evolution of defensive traits. Theoretical models show that the evolution of parasitism and the maintenance of mutualisms in multispecies interactions will depend on interactions with the host as well as with the defensive symbionts. At the community level, selection for defensive traits will vary greatly with ecological context and such spatial or temporal variation itself may stabilize defensive mutualisms. Studies of fungal endophytes within plant hosts demonstrate that endophytes acting as defensive mutualists may derive fitness benefits from the parasite as well as the host and suggest that interactions between co‐occurring symbionts within hosts may lead to the evolution of virulence.